Successful pregnancy after hCG/hMG treatment in an azoospermic male with idiopathic hypogonadotropic hypogonadism - Gyun-Ho Jeon; Cheyon Park (Indonesian Journal of Obstetrics and Gynecology, 2022)
Idiopathic hypogonadotropic hypogonadism (IHH) is one of the correctable causes of male infertility. Although there have been several previous reports about fertility treatment for IHH, there are no established guidelines of therapeutic method yet. We present an azoospermic male of IHH who succeeded in pregnancy and full term live birth after 18 months of treatment with human chorionic gonadotropin (hCG)/human menopausal gonadotropin (hMG), and then changed his treatment into testosterone replacement therapy to maintain an appropriate male hormone level. This case report shows that a thorough and careful examination of whether it is a reversible cause is necessary and important in the approach to male infertility. In addition, it further proves that, in the case of IHH, a continuous long-term gonadotrophic stimulation therapy contributes to successful pregnancy and may need a testosterone replacement therapy after birth.